Prevalence of multi-gastrointestinal infections with helminth, protozoan and Campylobacter spp. in Guatemalan children - Lauritz A. Jensen; Jerry W. Marlin; David D. Dyck; Harold E. Laubach (Journal of Infection in Developing Countries)
Background: The prevalence of multi-infections with helminthes, protozoans and Campylobacter spp. in Guatemalan children is a reflection of differences in the risk factors related to pathogen transmission. Methodology: Two hundred and eighty-nine fecal samples were collected from children of the Guatemalan highlands and patterns of pathogen occurrences were evaluated using an immunoassay for Campylobacter spp., a formalin-ether concentration followed by observation of unstained slides for helminthes and trichome stains of fecal smears for protozoans. Specimens were examined microscopically using 100, 400 and 1000x magnification. Results: Prevalence of Ascaris lumbricoides, Campylobacter spp., Giardia duodenalis, Entamoeba histolytica/E. dispar and Trichuris trichiura were 55.1%, 30.8%, 21.5%, 19.8% and 19.4%, respectively. Overall, the prevalence of at least one intestinal pathogen was 85.5%. Multi-infections were found in 43% of the children harboring pathogens. Conclusions: Infections with Campylobacter spp., E. histolytica/E. dispar, T. trichiura and G. duodenalis were closely associated with the presence of co-infection with A. lumbricoides. T. trichiura infection was related to co-infection with A. lumbricoides and Campylobacter spp. Infections with G. duodenalis and T. trichiura were related to co-infections with either Campylobacter spp. or E. histolytica/E. dispar. The prevalence of multi-gastrointestinal infections with helminthes, protozoans and Campylobacter spp. in children was found to be related to age and gender.